2017
DOI: 10.19084/rca16048
|View full text |Cite
|
Sign up to set email alerts
|

Armazenamento de mamão 'formosa' revestido à base de fécula de mandioca

Abstract: R E S U M ODe entre as tecnologias para reduzir as perdas da pós-colheita, o biofilme tem função de revestir o fruto impedindo as trocas gasosas entre o fruto e o ambiente. A fécula de mandioca é um biofilme de polissacárido tendo como principais vantagens o aumento da eficiência, resistência e baixo custo. O objetivo deste trabalho foi avaliar os efeitos da fécula de mandioca, como biofilme, aplicada em mamão (Carica papaya L.) da variedade 'Formosa' Thainung1, no 2º estado de maturação, tendo sido comparadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
4
4
0
11
Order By: Relevance
“…Souza et al (2014a) obtained an average of 0.09% of citric acid for papayas of the same variety, as well as found by Freitas et al (2018). Silva (2019) obtained mean values equal to 82 mg/100 g of vitamin C for fruits at the beginning of storage time, being found in this study an average of 38.01 mg/100 g. Nunes et al (2017) found mean values above 60 mg/100 g of vitamin C in Formosa papayas coated with cassava starch. The average pH was 5.21, which was the same as that found by Viana et al (2015).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Souza et al (2014a) obtained an average of 0.09% of citric acid for papayas of the same variety, as well as found by Freitas et al (2018). Silva (2019) obtained mean values equal to 82 mg/100 g of vitamin C for fruits at the beginning of storage time, being found in this study an average of 38.01 mg/100 g. Nunes et al (2017) found mean values above 60 mg/100 g of vitamin C in Formosa papayas coated with cassava starch. The average pH was 5.21, which was the same as that found by Viana et al (2015).…”
Section: Resultssupporting
confidence: 86%
“…There was little variation of pH between treatments, with T4 having the highest pH value, that is, fruits submitted to this treatment are less acid than those submitted to the other treatments. The mean pH was 5.34, a value close to that found by Nunes et al (2017), which obtained a mean pH of 5.3 for papaya fruits of the same cultivar (Formosa -'Tainung 01'). Already Teodosio et al (2018), when covering "Golden" papayas with microalgae and pomegranate seed oil, found average pH values between 4.8 and 5.2.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Existem diversas formulações de cobertura comestível dentre elas a base de fécula de mandioca, quitosana e amido, de acordo com Nunes et al (2017) a fécula de mandioca além de ser uma matéria prima de baixo custo, apresenta um ótimo custo-benefício, necessitando de estudos para determinação da melhor concentração para cada frutífera.…”
Section: Introductionunclassified